2001
DOI: 10.2308/accr.2001.76.3.357
|View full text |Cite
|
Sign up to set email alerts
|

The Mispricing of Abnormal Accruals

Abstract: This paper examines the market pricing of Jones (1991) modelestimated abnormal accruals (often termed “discretionary accruals” in the prior literature) to test whether stock prices rationally reflect the one-year-ahead earnings implications of these accruals. Using the Mishkin (1983) and hedge-portfolio test methods Sloan (1996) employs, I find that the market overestimates the persistence, or one-year-ahead earnings implications, of abnormal accruals, and consequently overprices these accruals. These results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

81
636
5
46

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 982 publications
(768 citation statements)
references
References 17 publications
81
636
5
46
Order By: Relevance
“…finds that across different industries or sets of firms, accruals persistence is unrelated to the strength of the accrual anomaly. 2,3 Some authors explicitly contend that the accrual anomaly represents in whole or part a rational risk premium, either for distress risk (Ng (2004)) or for the risks associated with the aggregate cash flow news factor and the discount rate news factor of Campbell and 1 See, e.g., Sloan (1996), Teoh, Welch and Wong (1998a,b), Collins and Hribar (2000), Xie (2001), Thomas and Zhang (2002), Mushruwala, Rajgopal and Shevlin (2004), and Hirshleifer et al (2004). 2 Zhang also finds that accruals covary strongly with firm growth attributes, which could be potentially consistent with either a behavioral or rational risk premium explanation.…”
Section: Introductionmentioning
confidence: 99%
“…finds that across different industries or sets of firms, accruals persistence is unrelated to the strength of the accrual anomaly. 2,3 Some authors explicitly contend that the accrual anomaly represents in whole or part a rational risk premium, either for distress risk (Ng (2004)) or for the risks associated with the aggregate cash flow news factor and the discount rate news factor of Campbell and 1 See, e.g., Sloan (1996), Teoh, Welch and Wong (1998a,b), Collins and Hribar (2000), Xie (2001), Thomas and Zhang (2002), Mushruwala, Rajgopal and Shevlin (2004), and Hirshleifer et al (2004). 2 Zhang also finds that accruals covary strongly with firm growth attributes, which could be potentially consistent with either a behavioral or rational risk premium explanation.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, there have been continuous discussions over the existence and causes of market anomaly where future stock returns might be predicted through variables related with finance and accounting information, such as unexpected earnings, accruals, and growth rate of long term operating assets Thomas 1989, 1990;Sloan 1996;Xie 2001;Fairfield, Whisenant, and Yohn 2003). Lev and Nissim (2004) expanded prior studies and reported that the investors failed to reflect BTD properly to predict future returns for the U.S. firms.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…In addition, we control for the market anomaly variable, which can directly affect future stock returns, unexpected earnings (SUE), accruals (ACC), the growth rate of long-term operating assets (GRLTNOA), and change of sales (CHSAL) (e.g., Thomas 1989, 1990;Fairfield, Whisenant, and Yohn 2003;Xie 2001). Finally, we include year dummies and industry dummies to control the influence of year by year effect and industry specific effect.…”
Section: Aver(vtmentioning
confidence: 99%
“…For net income, we use the definitions by Subramanyam (1996) and Xie (2001), which is the sum of accruals and cash flow from operations.…”
Section: Comparison Explanatory Power Of Earnings Componentsmentioning
confidence: 99%
“…Accordingly, investigating earning components under the accrual concept provides a means of understanding the executive's perspective of future earnings. Xie (2001) examine whether stock market rationally reflects these implications of accruals on enterprise's one-year-ahead earnings performance. Xie's study shows that the market overestimates the persistence of accrual components and overprices those stocks associated with abnormal accruals.…”
Section: Introductionmentioning
confidence: 99%